Δ-tocotrienol suppresses the migration and angiogenesis of trophoblasts in preeclampsia and promotes their apoptosis via miR-429/ ZEB1 axis. Issue 1 (1st January 2021) - Shi, Mei; Chen, Xiuyun; Li, Hui; Zheng, Lixia
ABSTRACT: Preeclampsia (PE) is a severe medical disorder during pregnancy and there has been controversy about the effects of vitamin E on PE. This research intended to explore if δ-tocotrienol (δ-TT), an isomer of vitamin E, could impact PE. Preeclamptic and normal placentas were obtained and total RNA was extracted. The expression of different genes was analyzed through quantitative real-time polymerase chain reaction (qRT-PCR) and Pearson correlation analysis was conducted. After that, HTR-8/SVneo cells (human trophoblasts) were chosen and they were subjected to δ-tocotrienol treatment and then Cell Counting Kit-8 was used to test cell viability. To assess the effects of δ-TT on trophoblasts, wound healing assay and Transwell invasion assay were performed. How miR-429 interacts with ZEB1 was examined via dual luciferase reporter assay. Also, protein expression was evaluated via Western blotting. Our results have shown that δ-TT can impair the viability of trophoblasts and induce their apoptosis. Additionally, it can repress the growth, migration, epithelial-mesenchymal transition (EMT), invasion and angiogenesis in trophoblasts. Mechanistically, δ-TT exerts these effects on trophoblasts via downregulating miR-429 and upregulating ZEB1. Furthermore, miR-429 can bind ZEB1 directly. Clinical sample analysis has revealed that miR-429 expression in preeclamptic placenta is higher than that in normal placenta, but ZEB1 expression in preeclamptic placenta is downregulated. Also, there is a negative association between miR-429 and ZEB1 expression in preeclamptic placentas. These discoveries imply that δ-TT may be hazardous to pregnancy and should not be used in preeclamptic patients. In addition, targeting miR-429 might treat PE.